Монголын төлөөлийн ба шууд ардчиллын асуудал түүнд тулгарч буй бэрхшээл, шийдвэрлэх арга зам - С.Базарпүрэв; У.Батцэрэн (Politology, 2024)
The common form of democracy such acceped by humans that regards to direct and representative democracy. In the reasson human lives, that those forms are dmeocratic connections with mutually complement to each other in a good challenges. According to the realities of Mongolian cases, those processes of democratic reform and its implementation such performs that reform process in 1990, has lost by ratio of both types of democrac such as direct and representative democracy in order to rather comes trough understaning of democracy and its proper form. But the consequences of citizens' political participation including representative and direct democracy', advantages and benefits disappearing eliminated to a negative effect on democracy as well as. Thus, the Department of Political Studies at the Institute of Philosophy from Academy of Sciences has been perfomed that themed basic research project on "Representative Democracy and citizens 'participation in Mongolia" in order to conduct that expert survey with a comprehensive review for this circumstances. Within this topic, we attempted to review on the crucial matter of democracy opportunities and challenges. Товч утга: Ардчиллын нийтлэг хэлбэр болох шууд ба төлөөллийн ардчилал нь харилцан холбогдож, бие биенээ нөхөн сэлбэж байдаг. Монгол оронд 1990 оноос хэрэгжиж буй ардчилсан өөрчлөлтийн үйл явцад ардчиллын дээрх хоёр хэлбэрийн харьцаа алдагдаж, шууд ардчилал гэхээсээ төлөөллийн ардчиллыг ардчиллын боломжтой, зохистой хэлбэр хэмээн үзэж ирсэн. Үүний уршгаар иргэдийн улс төрийн оролцоо тэр дундаа төлөөллийн болон шууд ардчиллын давуу болон үр өгөөжтэй талууд нь саармагжин үгүйрч, нийгэмд сөрөг нөлөө үзүүлж байна. Монгол Улсын Шинжлэх Ухааны Академийн Философийн хүрээлэнгийн Улс төр судлалын салбараас "Монгол Улс дахь төлөөллийн ардчилал ба иргэдийн улс төрийн оролцоо" сэдэвт суурь судалгааны төслийн хүрээнд шинжээчийн санал асуулга явуулан уг асуудлыг судлан түүний үр дүнд үндэслэн дээрх сэдвийн хүрээнд тухайн асуудлыг авч үзэхийг зорив.